Saccharomyces cerevisiae mannoproteins form an external cell wall layer that determines wall porosity. - Zlotnik, H (1984)
A beta-glucanase (Z-glucanase) from Zymolyase was freed from a protease (Z-protease) by affinity chromatography on alpha 2-macroglobulin-Sepharose columns and used to solubilize proteins from isolated cell walls of Saccharomyces cerevisiae. The cell wall proteins were labeled with 125I and subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis and autoradiography. The bulk of the labeled material had very low mobility. Its mannoprotein nature was demonstrated by precipitation with specific antibodies and by conversion to a band with an average molecular weight of 94,000 after incubation with endo-beta-N-acetylglucosaminidase. The intact mannoproteins were hydrolyzed by Z-protease, but were resistant to the enzyme when the carbohydrate was first removed by endo-beta-N-acetylglucosaminidase. In intact cells, lysis of cell walls by Z-glucanase required a previous incubation with z-protease, which led to solubilization of most of the 125I-labeled proteins. Other proteases that did not attack the cell wall mannoproteins were unable to substitute for Z-protease. The specific effect of Z-protease is consistent with the notion that mannoproteins form a surface layer of the cell wall that penetrates the wall to some depth and shields glucans from attack by Z-glucanase. Mannoproteins, however, do not appear to cover the inner face of the cell wall, because isolated cell walls, in contrast to intact cells, were completely solubilized by Z-glucanase in the absence of protease. The function of mannoproteins in determining cell wall porosity was highlighted by the finding that horseradish peroxidase (Mr, 40,000) causes lysis of cells that had been treated with Z-protease. Depletion of mannoproteins by Z-protease also resulted in the disappearance of a darkly stained surface layer of the cell wall, as observed by electron microscopy. Other agents that facilitate cell lysis by Z-glucanase, such as 2-mercaptoethanol, digitonin, and high concentrations of salts, caused little or no solubilization of mannoprotein. We assume that they perturb and loosen the structure of the mannoprotein network, thereby increasing its porosity. The implications of our results for the construction of the yeast cell wall and the anchoring of mannoprotein to the cell are discussed.